Polish‑German and Czech‑German Intra‑Industry Trade in Parts and Accessories for Motor Vehicles. a Comparative Analysis - Michalski, Bartosz (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The primary purpose of the paper is an identification of changes in relative trade advantages and intra‑industry trade between Poland, Czech Republic and Germany in the product cluster of parts and accessories for motor vehicles. The author conducts his research making use of trade data between 2001–2015 at the six‑digit disaggregation level and interprets the results using the paradigm of the middle‑income trap. Taking into account the context of ever growing fragmentation of corporate value chains, the first and foremost challenge for Poland and Czech Republic remains diversification of their exports regarding both goods as well as markets. The dominance of motor vehicle industry, including parts and accessories, deepens their technological dependence and does not support the process of increasing added value generated domestically.